Mechanisms underlying the therapeutic effects of Semen cuscutae in treating recurrent spontaneous abortion based on network pharmacology and molecular docking - Zheng, Wenfei; Lei, Manshu; Yao, Yao; Zhan, Jingqiong; Zhang, Yiming; Zhou, Quan (Frontiers in Molecular Biosciences, 2024)
Background: This paper aims to analyse the active components of SC by network pharmacology and screen the most stable compounds with TNF-a by molecular docking, to explore the mechanism of SC treatment of RSA and provide theoretical basis for drug development.:The active compounds of SC and the potential inflammatory targets of RSA were obtained from the Traditional Chinese Medicine Systematic Pharmacology Database and GeneCard, respectively. The interaction network of RSA-SC target gene was accomplished and Visualized by STRING database and Cytoscape software.GO and KEGG pathway enrichment analyses were obtained from DAVID to further explore the RSA mechanism and therapeutic effects of SC. Interactions between TNF-α and drugs were analysed by molecular docking.Sesamin and TNFa treatment of human trophoblast cells to detect proliferative and apoptotic abilities and WB assay to detect EGFR、PTGS2 and CASP3protein expression.Results: 10 compounds and 128 target genes were screened from SC, and 79 of them overlapped with RSA target inflammatory genes,which were considered as potential therapeutic targets. Network pharmacological analysis showed that sesamin, matrine, matrol and other SC compounds had good correlation with the inflammatory target genes of RSA.Related genes included PGR, PTGS1, PTGS2, TGFB1 and CHRNA7.Several signalling pathways are involved in the pathogenesis of RSA,sunh as TNF-α signaling pathway, HIF-1 signalling pathway, estrogen signaling pathway, proteoglycans in cancer , FoxO signalling pathway, etc. Molecular docking results